Cannabidiol reduces synaptic strength and neuronal firing in layer V pyramidal neurons of the human cortex with drug-resistant epilepsy - Martinez-Rojas, Vladimir A.; Márquez, Luis A.; Martinez-Aguirre, Christopher; Sollozo-Dupont, Isabel; López Preza, Félix Iván; Fuentes Mejía, Monserrat; Alonso, Mario; Rocha, Luisa; Galván, Emilio J. (Frontiers in Pharmacology, 2025)
The use of cannabidiol (CBD) as an alternative pharmacological approach for the symptomatic management of epilepsy has gained attention due to its potential efficacy, particularly in drug-resistant cases of epilepsy. Although multiple studies have described that CBD reduces neuronal hyperexcitability, the mechanistic basis of CBD remains a topic of ongoing research. In this study, we provide an electrophysiological portrayal of CBD’s effects on the glutamatergic transmission and intrinsic excitability of layer V pyramidal neurons of the human neocortex resected from drug-resistant epilepsy patients. The perfusion of CBD transiently depressed the field excitatory potential amplitude elicited in layer I/II and recorded in layer V without altering the paired-pulse ratio, suggesting a postsynaptic locus of action for CBD. Cortical slices perfused with 4-aminopyridine exhibited an increased number of spontaneous synaptic events that were abolished in the presence of CBD. At the cellular level, whole-cell patch-clamp recordings showed that CBD decreased the excitability of layer V pyramidal neurons, as evidenced by changes in the somatic input resistance, the membrane time constant, the hyperpolarization-induced “sag” conductance, the rheobase current needed to elicit an action potential, and the firing discharge in response to depolarizing current steps. Consistent with the last observation, CBD decreased the amplitude of the TTX-sensitive inward currents without altering the kinetics of the macroscopic outwardly directed currents. CBD washout restored the passive and active electrophysiological properties of pyramidal neurons. Collectively, these experiments demonstrate that CBD decreases the neuronal excitability of human cortical neurons from patients with drug-resistant epilepsy.